Effect of Filler Type and Content on the Rheological Properties of Asphalt Mastics - Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
This study investigated the influence of various fillers on the rheology and performance of asphalt mastics. Mastics were prepared by mixing a PG70-XX binder with two waste fillers (limestone sludge waste, glass powder) and conventional stone dust filler in three different proportions. Firstly, physical and chemical properties of fillers were determined and then asphalt concrete mixes were designed. Based on their optimum bitumen contents, the filler bitumen ratios were determined and mastics were prepared. The multiple stress creep and recovery (MSCR) test and linear amplitude sweep (LAS) analyses were performed to analyze the behavior of asphalt mastics against rutting and fatigue. In general, the use of waste fillers improved the rheological behavior of mastics in comparison to conventional stone dust mastic. The stiffness of all mastics increased with the filler bitumen ratio. The glass powder mastic displayed superior stiffness at all temperatures and exhibited higher elastic recovery and lower creep compliance. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.